If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(x+5)=28-3(6-x)
We move all terms to the left:
2(x+5)-(28-3(6-x))=0
We add all the numbers together, and all the variables
2(x+5)-(28-3(-1x+6))=0
We multiply parentheses
2x-(28-3(-1x+6))+10=0
We calculate terms in parentheses: -(28-3(-1x+6)), so:We get rid of parentheses
28-3(-1x+6)
determiningTheFunctionDomain -3(-1x+6)+28
We multiply parentheses
3x-18+28
We add all the numbers together, and all the variables
3x+10
Back to the equation:
-(3x+10)
2x-3x-10+10=0
We add all the numbers together, and all the variables
-x=0
x=0/-1
x=0
| (3x-3)(2x+6)=0 | | 4x+8+2x-22=22 | | 14.85=0.33x | | 10x+30-3x-9=-42 | | 8y-3=2y+1 | | x=88+112 | | 19g-11g=8 | | 11x-55+5x-20=-187 | | 9y+11=7y-24 | | 2x+3=180=x-6 | | 2y+12=2(y+6)* | | 12u-11u=10 | | 7z-z-1=35 | | 12u−11u=10 | | 1x+2+8x=-25 | | 0.8x+1=1.7x+0.1 | | 1a-7a=6 | | y=-9+15 | | C(x)=2x^2-24x+750 | | ×/10=x/11-9 | | 5+x=34.5 | | 9k-10k=1 | | x+2/2=1- | | 9+15g=3() | | 3(y-6)-y=2(y+9) | | 3y-4=y* | | 12=(3/4)x+6 | | x=4(6-6/3*2) | | 1-4v+6v=-17 | | 180=x-6 | | 2x+15=4x+9 | | 9x-14=7x#=6 |